Zombiekins - Bolger, Kevin; Blecha, Aaron (New York : Razorbill, 2010)
Stanley Nudelman buys a weird stuffed animal at the yard sale of a woman rumored to be a witch, and soon he and his friend Miranda are trying to save their schoolmates from becoming zombies.
Accelerated Reader AR
Keywords: Toys -- Juvenile fiction; Zombies -- Juvenile fiction; Occult fiction; Families -- Juvenile fiction; Zombiism -- Juvenile fiction; Stuffed animals (Toys) -- Juvenile fiction; Monsters -- Juvenile fiction; Schools -- Juvenile fiction; Students -- Juvenile fiction; Humorous stories